New antiviral compounds - Wiater, Elżbieta; Wiktor Jędrzejczak, Wiesław (Contemporary Oncology/Współczesna Onkologia, 2004)
The viruses from Herpesviridae family (Herpes simplex virus – HSV, Varicella-zoster virus – VZV and Human cytomegalovirus – HCMV) are common human pathogens. It is estimated that about 50-80% of adult population is infected by HSV-1 and 60-90% by HCMV. In the immunocompetent host, infections caused by Herpesviridae family viruses are usually asymptomatic. However, they create very serious and difficult clinical problems in immunocompromised patients. Frequencies of viral infections are constantly increasing because of the dynamic development of the anticancer chemo- and radiotherapy, the organ transplantation and the increasing number of HIV-positive patients. The antiviral drugs such as acyclovir (ACV), ganciclovir (GCV) and foscarnet (PFU) which are currently available in clinical practice in patients with impaired cellular immune functions have limited clinical usefulness. Drug resistance is growing as a result of long-term therapy especially in the case of prophylactic antiviral therapy. All these considerations justify the research for new antiviral agents that are less toxic, more effective and orally bioavailable. This article deals with new antiviral compounds, which are already in clinical practice or are the subject of clinical trials: – Herpes virus simplex (HSV 1 and 2) and varicella-zoster virus (VZV) – penciclovir, famciclovir, valacyclovir; – Human cytomegalovirus (HCMV) – valganciclovir, fomivirsen, cidofovir.